The The Students’ Difficulties in Understanding Reading Ability of Text at Eighth Grade Students of Mts Darussalamah Muda Sentosa Buay Madang Timur Kab. OKU Timur - Widiyanti, Anik; Franzhardi, Didi; Yahya, Yahya (English Education Program, Education Faculty, Universitas Nurul Huda, 2022)
This thesis is entitled “The Students’ Difficulties in Understanding Reading Skill of Text at Eighth Grade Students of MTs Darussalamah Muda Sentosa Buay Madang Timur Kab OKU Timur”. The problem of this study as follows: “What are the difficulties made by the students in understanding reading skill of text at eighth grade students of MTs Darusalamah Muda Sentosa Buay Madang Timur OKU Timur?” The objective of this thesis was to find out the difficulties made by the students in understanding reading skill of text at eighth grade students of MTs Darusalamah Muda Sentosa Buay Madang Timur OKU Timur. In this study, descriptive method was used. The population was all at the Eighth Grade Students of MTs Darussalamah Muda Sentosa Buay Madang Timur Kab OKU Timur, with the total number of the Students 68 Students. The sample was 32 Students taken through simple random sampling technique. The result of research showed that the students still got the difficultiess in used present perfect tense. The means score was gotten by the students only 67.96 in categorzed of moderate criteria. Although there was means of score was 95 reached by one studenst. And the lowest score was 50 was gotten by five students. The result of the tests at the eighth Grade Students of MTs Darussalamah Muda Sentosa Buay Madang Timur Kab OKU Timur. It shows that Based of calculation above, from students’ difficulties used narrative text and descriptive on text was 67.96%. It described that in using the “narrative text and descriptive text” the students have not understood yet, their mastery in using narrative text and descriptive text were moderate.